1994
DOI: 10.1007/bf01384904
|View full text |Cite
|
Sign up to set email alerts
|

Cultural specificity of approaches to studying in higher education: A literature survey

Abstract: Abstract. Students in higher education exhibit different approaches to learning, but there is evidence that these vary systematically from one culture to another. The broad distinction between an orientation towards comprehending the meaning of learning materials and an orientation towards merely reproducing those materials seems to be a universal feature of all systems of higher education. The former is both consistent and coherent, apparently reflecting the relatively high degree of agreement that exists acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
86
2
13

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(116 citation statements)
references
References 57 publications
13
86
2
13
Order By: Relevance
“…In most studies, a meaning-directed, a reproduction-directed, and an undirected pattern emerged, although these looked somewhat differently in different countries. This finding seems to support a previous observation by Richardson (1994) that a meaning and reproduction orientation to learning are universal across higher education systems but receive a specific interpretation in each system.…”
Section: Learning Patterns In New International Contexts and Populationssupporting
confidence: 91%
“…In most studies, a meaning-directed, a reproduction-directed, and an undirected pattern emerged, although these looked somewhat differently in different countries. This finding seems to support a previous observation by Richardson (1994) that a meaning and reproduction orientation to learning are universal across higher education systems but receive a specific interpretation in each system.…”
Section: Learning Patterns In New International Contexts and Populationssupporting
confidence: 91%
“…Qualitative and quantitative studies have confirmed a broad distinction between deep and surface approaches to learning (Entwistle and McCune 2004;Laurillard 1997;Ramsden 1997;Richardson 1994;Van Rossum and Hamer 2010;Watkins 1983). It has been widely recognized that the important distinction between these two approaches lies in the students' presence or absence of an intention to understand (Biggs 1987;Entwistle 2009;Kember 1996;Richardson 2000).…”
Section: Introductionmentioning
confidence: 95%
“…According to [4], the inability of schools and teachers to take account of preferences produces endemic low achievement and poor motivation. There are empirical researches as shown by [5], [6], [7] suggest that learning styles can enhance academic performance in several respects. Analyses of the learning styles of non-achieving students have revealed that, as a group, such students learn in a style and with instructional strategies that differ significantly from those of students who perform well in school [8].…”
Section: Introductionmentioning
confidence: 99%